Narrative theory IV: Within-subject effects of active and control scarcity narratives on delay discounting in alcohol use disorder - Craft, William H; Tegge, Allison N; Bickel, Warren K (Experimental and clinical psychopharmacology, 2022)
Imagining narratives involving sudden economic scarcity has been shown to increase delay discounting rates. However, previous studies have only compared active and control narratives between groups. Moreover, an investigation of the quantitative effects of different narrative scenario types has not been conducted. In this study, active and control scarcity narratives were administered within-subject in a sample of individuals meeting criteria for alcohol use disorder (AUD). Individuals with AUD (N = 81; 26.9% female) were recruited via Amazon Mechanical Turk. After assignment to the job (N = 42) or storm (N = 39) narrative groups, participants completed delay discounting tasks while imagining an active (job loss/hurricane) and control (job neutral/mild storm) condition. Both active narratives increased delay discounting relative to the corresponding control condition (p < .001), with no effect of order of presentation (p = .202). Additionally, both narrative types exerted similar effect sizes on discounting rates (job: d = 0.54; storm: d = 0.45). This study replicates and extends previous research on the manipulability of delay discounting rates with scarcity narratives. We demonstrated that the active narrative significantly increased delay discounting relative to a control narrative within-subject, regardless of presentation order. Moreover, both the job loss and hurricane narratives exerted a similar effect on the delay discounting rate. These results highlight the robust ability of the Narrative Theory framework to shift delay discounting rates and suggest that in AUD, imagining economic scarcity due to job loss or hurricane exerts comparable effects on behavioral economic decision-making. (PsycInfo Database Record (c) 2022 APA, all rights reserved).Imagining narratives involving sudden economic scarcity has been shown to increase delay discounting rates. However, previous studies have only compared active and control narratives between groups. Moreover, an investigation of the quantitative effects of different narrative scenario types has not been conducted. In this study, active and control scarcity narratives were administered within-subject in a sample of individuals meeting criteria for alcohol use disorder (AUD). Individuals with AUD (N = 81; 26.9% female) were recruited via Amazon Mechanical Turk. After assignment to the job (N = 42) or storm (N = 39) narrative groups, participants completed delay discounting tasks while imagining an active (job loss/hurricane) and control (job neutral/mild storm) condition. Both active narratives increased delay discounting relative to the corresponding control condition (p < .001), with no effect of order of presentation (p = .202). Additionally, both narrative types exerted similar effect sizes on discounting rates (job: d = 0.54; storm: d = 0.45). This study replicates and extends previous research on the manipulability of delay discounting rates with scarcity narratives. We demonstrated that the active narrative significantly increased delay discounting relative to a control narrative within-subject, regardless of presentation order. Moreover, both the job loss and hurricane narratives exerted a similar effect on the delay discounting rate. These results highlight the robust ability of the Narrative Theory framework to shift delay discounting rates and suggest that in AUD, imagining economic scarcity due to job loss or hurricane exerts comparable effects on behavioral economic decision-making. (PsycInfo Database Record (c) 2022 APA, all rights reserved).